Global Futures, Global Citizens and Enhancing the Student Experience: A Curtin Model - Fozdar , Farida (Acta Pedagogia Asiana, 2026)
This paper explores a number of initiatives of Curtin University’s Faculty of Humanities designed to respond to the changing tertiary environment, new opportunities for improving the student experience, and a growing recognition of the need to graduate globally competent citizens. It describes two initiatives: a new graduate degree aimed at producing globally-aware, interdisciplinarily competent, real-world-ready graduates; and a pilot project implementing challenge-based learning focused on topics relevant to sustainability, indigenous knowledge, learning, and global futures. In 2022, the Faculty introduced four capability platforms with the goal of breaking down disciplinary silos. These platforms are designed to experiment with new methods of learning and to enhance engagement and research opportunities. In a related move, the Faculty introduced a new Master of Global Engagement in 2024, which employs an innovative stacked structure combining a new Graduate Certificate in Global Engagement with existing Graduate Certificates to provide greater disciplinary flexibility and more global perspectives. Each initiative incorporates digital integration in multidisciplinary curriculum design, along with a range of other pedagogical innovations. This paper outlines the initiatives, the rationale and impetus driving these innovations, and initial reflections on their success.